1-(2-Hydroxyethyl)-5-mercapto-1H-tetrazole as ligand in Cu(I) complexes with or without X-ions (X = Cl, Br, I): synthesis, crystal structures and properties. Issue 21 (2nd November 2017) - Zhang, Xiao-Yu; Su, Chao-Hong; Pang, Hua-Yu; Huang, Fu-Ping; Yu, Qing; Bian, He-Dong
Abstract: Four Cu(I) complexes with 1-(2-hydroxyethyl)-5-mercapto-1H-tetrazole (Hhmt) as a ligand, [Cu(hmt)]n (1 ), [Cu2 Cl(hmt)]n (2 ), [Cu4 Br(hmt)3 ]n (3 ), and [Cu4 I(hmt)3 ]n (4 ), have been synthesized. In1 –4, hmt adopts a μ 4 - η 1  :   η 1  :   η S 2 coordinate mode to join the adjacent Cu(I) ions, which form different two-dimensional (2-D) structures. In1, the neighboring four Cu(I) atoms are connected by μ 4 -hmt to form a 2-D structure. In2, the Cu(I) ions are firstly connected with Cl ions to form a 1-D [Cu4 Cl2 ] subunit chain, which then have been bridged by hmt to form a 2-D structure. However, the inorganic [Cu4 Br] and [Cu4 I] motifs are respectively connected by hmt to form 2-D structures in isostructural3 and4 . In addition, the fluorescent properties and the thermal stability properties of1 –4 have been investigated. Abstract :